3D Printed Microfluidic Mixers—A Comparative Study on Mixing Unit Performances. Issue 2 (10th December 2018) - Enders, Anton; Siller, Ina G.; Urmann, Katharina; Hoffmann, Michael R.; Bahnemann, Janina
Abstract: One of the basic operations in microfluidic systems for biological and chemical applications is the rapid mixing of different fluids. However, flow profiles in microfluidic systems are laminar, which means molecular diffusion is the only mixing effect. Therefore, mixing structures are crucial to enable more efficient mixing in shorter times. Since traditional microfabrication methods remain laborious and expensive, 3D printing has emerged as a potential alternative for the fabrication of microfluidic devices. In this work, five different passive micromixers known from literature are redesigned in comparable dimensions and manufactured using high‐definition MultiJet 3D printing. Their mixing performance is evaluated experimentally, using sodium hydroxide and phenolphthalein solutions, and numerically via computational fluid dynamics. Both experimental and numerical analysis results show that HC and Tesla‐like mixers achieve complete mixing after 0.99 s and 0.78 s, respectively, at the highest flow rate (Reynolds number ( Re ) = 37.04). In comparison, Caterpillar mixers exhibit a lower mixing rate with complete mixing after 1.46 s and 1.9 s. Furthermore, the HC mixer achieves very good mixing performances over all flow rates ( Re = 3.7 to 37.04), while other mixers show improved mixing only at higher flow rates. Abstract : One of the most basic operations of microfluidics is mixing . In this work, four different passive micromixer designs are fabricated using high‐definition 3D printing, and their mixing performances are compared experimentally and numerically. The most efficient mixers are the Tesla‐like and HC designs, with the HC design showing the most reliable performance over a range of Reynolds number.